2013
DOI: 10.1016/j.biortech.2013.02.088
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal microwave processing of microalgae as a pre-treatment and extraction technique for bio-fuels and bio-products

Abstract: Microalgae are regarded as a promising source of lipids for bio-diesel production and bioproducts. The current paper investigates the processing of microalgal slurries under controlled microwave irradiation. Microwave power was applied to reach temperatures of 80, 100, 120 and 140°C at a constant residence time of 12 min. Microwave irradiation led to disruption of the algal cell walls which facilitated lipid extraction. The influence of inorganic material on microwave heating was assessed for three strains inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 24 publications
(21 reference statements)
1
35
0
1
Order By: Relevance
“…This has raised the question as to whether it is possible to extract nitrogen-containing components prior to high-temperature HTL (which is carried out typically at temperatures in the range of 300 to 350°C). In particular, reductions in nitrogen contents of the final bio-crude product are achieved through an initial mild HTL (temperatures b 200°C) as a preliminary treatment, albeit with concomitant reduction in the quantity of the bio-crude generated [12][13][14][15]. While these results are promising, the relationships between quality and quantity of the bio-crude produced in such two-stage treatments are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This has raised the question as to whether it is possible to extract nitrogen-containing components prior to high-temperature HTL (which is carried out typically at temperatures in the range of 300 to 350°C). In particular, reductions in nitrogen contents of the final bio-crude product are achieved through an initial mild HTL (temperatures b 200°C) as a preliminary treatment, albeit with concomitant reduction in the quantity of the bio-crude generated [12][13][14][15]. While these results are promising, the relationships between quality and quantity of the bio-crude produced in such two-stage treatments are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [7e12] employed the Bligh and Dyer method [13], which uses chloroform, methanol, and water as co-solvents for extracting and purifying lipids. Additionally, other solvent systems have been investigated as possible extracting solvents, including dichloromethane/methanol/water [14], dichloromethane/water [15], nhexane/water [12], and ethanol/water and hexane/water [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several pretreatment methods have been investigated to improve the efficiency of solvent extraction systems, including ultrasonication [7e12, 14,17], microwave [7e11, 14,15], electroporation [18], and bead mills, autoclave and osmotic pressure [7]. These studies reported a significant increase in the quantity of lipids extracted due to pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat in the cell suspension results from rotation and vibration of dipolar molecules and ions in an electromagnetic field (Biller et al 2013). Advantages include short residence/processing time, scalability, high efficiency, low energy consumption, and low risk of metabolite denaturation (Günerken et al 2015;Biller et al 2013;Pasquet et al 2011).…”
Section: Non-mechanical Methodsmentioning
confidence: 99%